Pengembangan Domain Ontologi Studio Apartement - kresnawan, Lanang Ary; Adi Pramartha, Cokorda Rai (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
Bali is one of the provinces in Indonesia with its capital in Denpasar. Bali is well-known as a tourism destination with its unique arts and culture. For people who go to Bali to continue their education or work on work projects, they definitely need a place to stay while in Bali. Not infrequently many of them choose to rent this studio apartement because the facilities offered are adequate for them to live in Bali. However, because many of them come from outside the island of Bali, they don't know where to look for places or locations that provide these services. Lack of information about places that provide this service is one of the problems faced. Therefore, ontology can be used to provide information related to studio apartement explicitly by using the semantic ontology approach, because ontology is able to handle more complex data and is able to apply data-links, so that data can be integrated into various systems that have similar domains. built has 9 classes, 4 object properties and 14 individuals.